Cut‐Off Values for Transit Time Flowmetry: Are the Revision Criteria Appropriate?1. Issue 1 (28th November 2012) - Une, Dai; Deb, Saswata; Chikazawa, Genta; Kommaraju, Kamya; Tsuneyoshi, Hiroshi; Karkhanis, Reena; Singh, Steve; Vincent, Jessica; Tsubota, Hideki; Sever, Jeri; Moussa, Fuad; Cohen, Gideon; et al.
Abstract Background: Graft Imaging to Improve Patency (GRIIP), a single‐center, randomized blinded clinical trial, reported that intraoperative graft assessment with graft revision according to a priori criteria of transit time flowmetry (TTF) and intraoperative fluorescent angiography did not improve graft patency at one year after coronary artery bypass grafting (CABG) when compared with standard intraoperative management. The objective of this study is to investigate whether other TTF values are more predictive of the saphenous vein graft (SVG) failure and/or clinical outcomes. Methods: This is a case control retrospective study of 65 SVGs from 44 patients from GRIIP. Study outcomes were graft patency at 12 months and major adverse cardiac events (MACE; death, myocardial infarction, repeat revascularization). Results: Twenty‐two SVGs were occluded. In receiver operating characteristic curve analysis, TTF mean flow was significantly predictive of one‐year SVG failure (area under the curve = 0.698, p < 0.01), and 31 mL/min was the best cut‐off value (p = 0.017, sensitivity 63.6%, specificity 67.4%). The risk of graft occlusion was 14/28, 50% for grafts with mean flow <31 mL/min and 8/37, 21.6% for grafts with mean flow ≥31 mL/min. In logistic regression models, mean flow was a significant predictor of early SVG failure (Odds Ratio 0.95 [0.91–0.99] per mL/min, p = 0.014) whereas other TTF values, patient comorbidities, and/or medication at discharge were not. However, TTF values were not predictive of MACE. Conclusions: TTF can identify non‐functional grafts during CABG, but is of questionable value to improve one‐year graft patency.